2007
DOI: 10.15288/jsad.2007.68.192
|View full text |Cite
|
Sign up to set email alerts
|

Association of ALDH1 Promoter Polymorphisms With Alcohol-Related Phenotypes in Trinidad and Tobago*

Abstract: Now welcome, the most inspiring book today from a very professional writer in the world, association of aldh1 promoter polymorphisms with alcohol related phenotypes in trinidad and tobago a. This is the book that many people in the world waiting for to publish. After the announced of this book, the book lovers are really curious to see how this book is actually. Are you one of them? That's very proper. You may not be regret now to seek for this book to read. This inspiring book becomes one that is very booming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The median age for each study was calculated as follows: ([upper age -lower age]/2) + lower age. Four publications reported only the mean age (8,35,82,86). For these studies, we used the mean age as an estimate of the median age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age for each study was calculated as follows: ([upper age -lower age]/2) + lower age. Four publications reported only the mean age (8,35,82,86). For these studies, we used the mean age as an estimate of the median age.…”
Section: Discussionmentioning
confidence: 99%
“…There were 27 studies conducted in nine countries that reported data for HBV or HCV infection (n = 100,031) (26-29, 34-40, [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Three different markers were utilized to evaluate exposure to HBV infection (Hepatitis B surface antigen (HBsAg); Anti-Hepatitis B surface antigen (Anti-HBsAg) and Anti-Hepatitis B core antigen (Anti-HBcAg)).…”
Section: Hepatitis B Virus/hepatitis C Virus (Hbv/hcv)mentioning
confidence: 99%
“…Aldh1a1 has been previously implicated in brain development [Denisenko-Nehrbass et al, 2000], schizophrenia [Galter et al, 2003], and alcoholism [Moore et al, 2007]. An intriguing finding is that of Oprm1 (opioid receptor mu 1) as a top candidate gene for bipolar.…”
Section: Ncam1mentioning
confidence: 99%
“…The ALDH1A1*2 allele has been identified in diverse ethnic populations, including, Asians, Caucasians and African-Americans, while ALDH1A1*3 has only been discovered thus far in African-Americans, Mission Indians and Afro-Trinidadians. [3,21,24]…”
Section: Resultsmentioning
confidence: 99%
“…[23] The frequency of genotypes of alcohol metabolism in this population was unknown until recently. A study was undertaken that evaluated associations of ALDH1A1 promoter polymorphisms with alcohol-related phenotypes in this population [24]. In that study, the allele frequencies for ALDH1A1*1 , ALDH1A1*2 and ALDH1A1*3 in Afro-Trinidadians were found to be 0.941, 0.035 and 0.024, respectively, and 0.926, 0.074 and 0.000 in Indo-Trinidadians.…”
Section: Introductionmentioning
confidence: 99%